THE ROLE OF APOPTOSIS IN CHRONIC MYELOPROLIFERATIVE NEOPLASMS - Jakhonov Azizbek Kholmirzaevich; Matkarimova Dilfuza Saburovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Chronic myeloproliferative neoplasms (MPNs) are clonal hematologic disorders arising from hematopoietic stem cells and characterized by sustained proliferation of myeloid lineage cells. These diseases, including polycythemia vera, essential thrombocythemia, and primary myelofibrosis, are commonly associated with recurrent molecular abnormalities such as JAK2, CALR, and MPL mutations. While enhanced proliferative signaling is a defining feature of MPNs, increasing evidence highlights dysregulation of apoptosis as a key contributor to their pathogenesis. Apoptosis is a tightly regulated biological process essential for maintaining hematopoietic homeostasis through the elimination of damaged or genetically unstable cells. In MPNs, impairment of intrinsic and extrinsic apoptotic pathways results in resistance to programmed cell death, promoting prolonged survival and accumulation of abnormal myeloid progenitor cells in the bone marrow and peripheral blood. Altered expression of critical apoptotic regulators, including upregulation of anti-apoptotic proteins and suppression of pro-apoptotic factors, plays a significant role in disease persistence, clinical heterogeneity, and progression to advanced disease stages. This review summarizes the molecular mechanisms of apoptosis, outlines the major apoptotic alterations observed in chronic myeloproliferative neoplasms, and discusses their clinical and prognostic implications. Understanding apoptosis-related dysregulation in MPNs may facilitate improved risk stratification and support the development of targeted therapeutic strategies aimed at restoring programmed cell death in malignant hematopoietic cells